Study of Some Biochemical Values Changes Associated With Morphological Anemia in Local Breed Goats: RaadMahmood Hussein1and. KefahOda Salman Al-jeburii2 - Hussein, Raad Mahmood (The Iraqi Journal of Veterinary Medicine, 2012)
This study was conducted on local breed goats to determine the changes in biochemical parameters in anemic cases by using morphological classification, one hundred and seventyserum samples were collected randomly from goats of both sexes aged 3 months – 6 years, they were grazing on pasture from the different districts of Baghdad, Bakuba and Falluja. The total protein, albumin and fibrinogen in the normal bucks were 73 1 – 84 1 g/L, 35 3- 37 1 g/ L, 9 8- 11 1 g/ L, respectively and in the normal does were 66 1 – 77 4 g/ L, 35 6 – 37 2 g/ L and 6 – 15 g/ L, respectively, the average of these parameters differed significantly at (p> 0.05) between the normal and the anemic animals. The mean level of copper in the serum of normal goats was 21.66 µmol/L and the the mean level of iron in serum was 29.24 µmol/L these averages value were declined in the anemic goats was significantas compared with apparently healthy goats.